1986
DOI: 10.1007/bf01243361
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient intake, plasma large neutral amino acids and mood during weight-reducing diets

Abstract: Influence of diet composition on mood during weight-reducing diets was studied in healthy young women of normal weight. A broad range of macronutrient intake was achieved by means of divergent dietary instructions for the composition of a 1,000 kcal per day diet adhered to for six weeks. Global mood during the last three weeks of the diet was significantly better in the "vegetarian" than in the "mixed" diet group. During this time a significant correlation was observed between relative carbohydrate intake and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Therefore, it is likely that the effects of weight loss may have had dominant effects on mood that overshadowed any effect of diet composition. However, Schweiger et al (37) showed in normalweight young women that mood was significantly better after 6 wk of an energy-restricted diet higher in carbohydrate and lower in fat and protein. Hence, the possible protection of weight loss against any otherwise negative effects of dietary composition may be confined to overweight or obese persons.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that the effects of weight loss may have had dominant effects on mood that overshadowed any effect of diet composition. However, Schweiger et al (37) showed in normalweight young women that mood was significantly better after 6 wk of an energy-restricted diet higher in carbohydrate and lower in fat and protein. Hence, the possible protection of weight loss against any otherwise negative effects of dietary composition may be confined to overweight or obese persons.…”
Section: Discussionmentioning
confidence: 99%
“…So endogenous plasma tryptophan and tyrosine to large neutral amino acid (LNAA) ratios could modify, among many other functions, via respectively the serotoninergic and catecholaminergic pathways, the food se lection, food intake and energy balance [Möller, 1986b]. Relations between affective disorders and feeding be havior are complex [Möller, 1986a;Schweiger et al. 1986;Morley and Blundell, 1988].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Schweiger et al (1986a) found that better mood was associated with higher average 24-h plasma TRP : LNAA. Nevertheless, more chronic studies of this type are needed before definitive conclusions can be drawn: for instance, both mood and TRP : LNAA could be raised by poor compliance with the required energy restriction.…”
Section: Effects Of Chronic Dietary Manipulations On Mood and Performmentioning
confidence: 99%
“…Despite these methodological caveats, two other studies have linked greater positive affect and less negative affect with chronic (9 d or 6 weeks) relatively high-carbohydrate and lowprotein intake (Schweiger et al 1986a;De Castro, 1987b), although performance was not measured. Furthermore, Schweiger et al (1986a) found that better mood was associated with higher average 24-h plasma TRP : LNAA.…”
Section: Effects Of Chronic Dietary Manipulations On Mood and Performmentioning
confidence: 99%